1992
DOI: 10.1007/bf00201635
|View full text |Cite
|
Sign up to set email alerts
|

Fungal elicitors induce a transient release of active oxygen species from cultured spruce cells that is dependent on Ca2+ and protein-kinase activity

Abstract: Cell-wall components from the ectomycorrhizal fungi Amanita muscaria and Hebeloma crustuliniforme and from the spruce pathogen Heterobasidion annosum elicited a transient release of active oxygen species from cultured spruce cells (Picea abies (L.) Karst.). Since the detection of active oxygen was suppressed by catalase, H2O2 was assumed to be the prevailing O2 species. On the other hand, superoxide dismutase enhanced the concentration of detectable H2O2 indicating that the superoxide anion was formed before d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
160
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(171 citation statements)
references
References 39 publications
11
160
0
Order By: Relevance
“…We found that washing and equilibration of cells were essential to reduce high levels of AOS in non-elicited cells. This has been observed with other species [14,16,22], possibly due to substances that interfere with CL. Moreover, mechanical agitation of cells may also induce AOS production [23,24].…”
Section: Resultssupporting
confidence: 62%
“…We found that washing and equilibration of cells were essential to reduce high levels of AOS in non-elicited cells. This has been observed with other species [14,16,22], possibly due to substances that interfere with CL. Moreover, mechanical agitation of cells may also induce AOS production [23,24].…”
Section: Resultssupporting
confidence: 62%
“…In plants, protein phosphorylation was shown to play a direct regulatory role in light response (for reviews, see Bennett, 1991;Alien, 1992) and circadian rhythms (Carter et al, 1991). Correlations between protein phosphorylation and physiological response were demonstrated in pollen embryogenesis (Kyo and Harada, 1990) and fungal elicitor treatment of cultured cells (Grab et al, 1989;Dietrich et al, 1990;Grosskopf et al, 1990;Felix et al, 1991;Schwacke and Hager, 1992). Here, with the use of specific kinase and phosphatase inhibitors, we show that phosphorylation events are essential for the ethylene-mediated pathogenesis response in tobacco plants.…”
Section: Introductionmentioning
confidence: 61%
“…A requirement for calcium influx for subsequent signaling events has been demonstrated in at least some systems (Schwacke and Hager, 1992;He et al, 1993;Nurnberger et al, 1994;Hahlbrock et al, 1995;Tavernier et al, 1995). Anion channel blockers prevent activation of the oxidative burst and defense gene transcription in parsley cells treated with fungal elicitor (T. Jabs and D. Scheel, personal communication).…”
Section: A Sum Of Signalsmentioning
confidence: 99%